DEMiR YUKLEMESiNiN PLAZMA BAKIR VE CiNKO DUZEYLERiNE ETKiSi - YİĞİT, Günnur; SEYMEN, Pınar; ÖZÇELİK, Derviş; GÜLYAŞAR, Tevfik; MENGİ, Murat; SEYMEN, H. Oktay (Cerrahpaşa Medical Journal, 2019)
Background and design.- The harmful effects of acute and chronic iron loading are well documented. Increased lipid peroxidation is an important expression of both chronic and acute iron toxicity. In the structure of some antioxidant enzymes such as SOD, the copper and the zinc are im.ulved. Our aim was to study the effect of iron overloading on the plasma copper and zinc levels. Results.- Adult male Wistar albino rats weighing 200-205g were used. The animals were divided into 2 weight-matched groups. Group 1: Control group (n=6) and Group 2: Iron overloading group (n=7). The rats of group 2 received intraperitoneal iron (Ferro Ill hydroxide polymaltose) at a dose of 250 mg/kg/day for 10 days. At the end of the administration period, the rats were killed under ketamine ariesthesia (50 mg/kg). Heparinized blood samples were obtained from aorta abdominalis. The plasma iron, copper and ziric levels were mesaured by atomic absorbtion spectrophotometer. The plasma free iron values for rats receiving iron were significantly (p<0.001) higher. This finding confirmed the establishment of the iron overloading state. The plasma free copper levels of iron overloading group were higher (p<0.01) than those of control rats. There was no significant difference between the plasma zinc levels of two groups (P>0.05). Conclusion.- We concluded that the trace elements such as copper and zinc have very important effects on the oxidant/antioxidant status of the organism. These are: 1- High iron levels of the plasma under iron overloading condition indicate the oxidant status in the organism. 2- The plasma cu+ levels increase iron overloading condition. This contributes to the metabolic activation of the antioxidant enzymes such as SOD. 3- The plasma Zn+ concentrations of two groups are almost the same levels. This impact may be due to overutilization of zinc ions in iron overloading group.